Pembuatan Aplikasi Pencatatan Alat K3 Dan Apd Berbasis Mobile Menggunakan Qrcode - Arief Dzul Qani; M. Farman Andrijasa; Subhan Hartanto (JURNAL VOKASI TEKNIK, 2024)
Recording and tracking of K3 (Occupational Safety and Health) and PPE (Personal Protective Equipment) tools in the IT Service Business Partner Department at PT. Pupuk Kalimantan Timur is currently done manually, which can cause inefficiency and the risk of data loss. To overcome this problem, a mobile application has been developed that uses QR Code technology to improve the accuracy and efficiency of recording. This application is built using the Flutter framework and Dart programming language with the waterfall methodology, and utilizes Firebase as a database to support real-time data updates. Application testing was carried out using the blackbox method, and the results showed an increase in accuracy and speed of recording compared to the manual method. The user satisfaction level reached 86%, indicating that this application is in accordance with user expectations and is worthy of being implemented widely.